Unconventional elastomeric isolators reinforced with engineered plastic plates: compressive failure analysis. (November 2021) - Tan, Ping; Liu, Han; Donà, Marco
Highlights: Unconventional Engineered-Plastic-Plate Reinforced Elastomeric Isolators (EPPREIs). Compressive failure analysis of EPPREIs and evidence of various failure types. Analytical solutions to stresses and to compression and bending moduli of EPPREIs. Compressive strength prediction equations associated with various types of failure. Failure domains based on shear bond strength/plate strength for cost-effective design. Abstract: This paper investigates the compression behaviour of engineered-plastic-plate reinforced elastomeric isolators (EPPREIs), which use engineered plastic plates instead of steel reinforcements as in conventional isolators. Compared to the latter, EPPREIs are cheaper, lighter and easier to install. Experimental tests showed that EPPREIs can undergo different types of failure: buckling, delamination and reinforcement failure. Buckling is typical for conventional isolators, and analytical solutions are available for its prediction; however, they depend on the bending modulus, which must be specifically determined for EPPREIs. Furthermore, there are no specific analytical solutions to predict the other failure types. Therefore, a theory to evaluate the compressive failure behaviour of EPPREIs is developed in this paper with the aim of supporting their design. In particular: governing equations under vertical compression and simple bending are established while assuming an orthotropic reinforcement and including the rubber compressibility; solutions to the problem of stresses in the rubber and reinforcement layers as well as compression and bending moduli are obtained; prediction equations are derived for the compressive strengths associated with the various failure types. Parametric finite element analyses, compression-shear tests and compressive failure tests are conducted to validate this theory. Finally, indications are provided for a cost-effective design of EPPREIs.